2016
DOI: 10.1016/j.atherosclerosis.2016.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Ex-vivo imaging and plaque type classification of intracranial atherosclerotic plaque using high resolution MRI

Abstract: Background and Aims Recent development of high resolution MRI techniques have enabled imaging of intracranial atherosclerotic plaque in vivo. However, identifying plaque composition remains challenging given the small size and the lack of histological validation. This study aims to quantify the relaxation times of intracranial plaque components ex vivo at 3T and to determine whether multi-contrast MRI could classify intracranial plaque according to the American Heart Association classification with histologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 29 publications
0
45
0
1
Order By: Relevance
“…Since no tissue can be obtained while the patient is alive-compared with, for example, endarterectomy samples in carotid artery disease-validation can only be performed in postmortem studies. A series of postmortem validation studies has been performed at 7 T by using ex vivo circle of Willis specimens from patients with and without a history of cerebrovascular disease, as well as from patients with intracranial aneurysms (47,(67)(68)(69)(70)(71). These studies found clear correlations between VW and atherosclerotic plaques detected on VW images and histopathologic findings, best seen on T1-weighted data and, thus, shorter imaging times.…”
Section: Clinical Considerationsmentioning
confidence: 89%
See 1 more Smart Citation
“…Since no tissue can be obtained while the patient is alive-compared with, for example, endarterectomy samples in carotid artery disease-validation can only be performed in postmortem studies. A series of postmortem validation studies has been performed at 7 T by using ex vivo circle of Willis specimens from patients with and without a history of cerebrovascular disease, as well as from patients with intracranial aneurysms (47,(67)(68)(69)(70)(71). These studies found clear correlations between VW and atherosclerotic plaques detected on VW images and histopathologic findings, best seen on T1-weighted data and, thus, shorter imaging times.…”
Section: Clinical Considerationsmentioning
confidence: 89%
“…reduce acquisition time in 3D TSE sequences, while the trajectories can also be optimized for reduced T2 weighting (17,23). Compressed sensing allows image reconstruction from fewer k-space sequences (47,67,68,70,71). However, more insight into what normal ageing of the VW looks like on VW images and what underlying mechanisms can cause VW (lesion) enhancement are still needed.…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…The time between death and the postmortem examination was Ͻ1 month; however, the exact time window was unknown due to the limitations of our local ethics committee. The same specimens were evaluated in a previous study 18 ; however, the current study addresses distinctly different research questions, specifically performing a quantitative analysis of the identification of plaque components on multicontrast imaging. The demographics of the cadavers were reported in the previous publication.…”
Section: Study Populationmentioning
confidence: 99%
“…The demographics of the cadavers were reported in the previous publication. 18 All specimens were rinsed carefully with saline to remove blood clots. The same pathologist excised possible atherosclerotic arteries according to gross morphologic changes.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation